Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/agj2.20124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of defoliation and row spacing on intermediate wheatgrass II: Forage yield and economics

Abstract: Management systems that produce both grain and biomass coproducts could enhance the profitability of the novel perennial grain crop Kernza intermediate wheatgrass [Thinopyrum intermedium (Host) Barkworth & D.R. Dewey] (IWG). Harvesting IWG for grain typically results in a straw harvest; in addition, vegetative biomass can be cut in spring, fall, or both for hay production. We evaluated the interacting effects of defoliation and row spacing on yield, forage quality, and economic return across the 3-yr life of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 45 publications
5
42
2
Order By: Relevance
“…While they did not report yield plant -1 , similar decreases over time in yield spike -1 , seed mass, seed dimensions, florets spikelet -1 , and stem width were observed, though whether this decrease occurred between the second or third year was variable depending on the trait. A study of IWG yield components in sward environments also reported a 50% reduction in grain number per spike after the first year (Hunter et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…While they did not report yield plant -1 , similar decreases over time in yield spike -1 , seed mass, seed dimensions, florets spikelet -1 , and stem width were observed, though whether this decrease occurred between the second or third year was variable depending on the trait. A study of IWG yield components in sward environments also reported a 50% reduction in grain number per spike after the first year (Hunter et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…However, the reduction in grain yield following defoliation in 2017, which likely resulted from a reduction in spikes/tillers and grains spike −1 , suggests that repeated defoliation may ultimately diminish stand vigor and grain yield. This may be due in part to depletion of N reserves (see Hunter et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is unclear, since these well‐established stands should have required lower investment in root growth than the first‐year stand. This suggests that reproductive growth may be declining due to other factors, such as genetic control, nutrient limitation (see Hunter et al., 2020), or disease burden.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations